2017
DOI: 10.25135/jcm.6.17.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Determination and validation method of molybdenum by adsorptive catalytic stripping voltammetry at lead film electrode

Abstract: Abstract:A new, selective, sensitive and accurate method for determination of molybdenum by adsorptive catalytic stripping voltammetry was described. The method is based on catalytic reduction of adsorbed Mo(VI)-ARS complex onto the lead film electrode in the presence of chlorate used as oxidizing agent. The instrumental and solution parameters affecting the peak current were optimized. The calibration graph is linear between 2.65-20.00 µg/L Mo(VI) and limit of detection is estimated as 0.79 µg/L. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The symmetry of the electrode reaction was investigated by calculating the charge transfer coefficient ( α ) using the slope ( 2.3RT/[]1-αnF ${2.3RT/\left[\left(1-\alpha \right)nF\right]}$ ) of Ep4pt()mV- ${{E}_{p}{\rm \ }\left(mV\right)-}$ boldlboldoboldg(v,4ptmV/s) ${{\bf log}(v,{\rm \ }mV/s)}$ curve (Ep=97.40log(v)+ $({{E}_{p}=97.40{\bf log}(v)+}$ 692.90 $692.90$ (R 2 : 0.981)), and α was determined as 0.697 (Figure S4). This indicates an asymmetric behavior of the transition state regarding the applied potential, acting akin to a product‐like transition state [26, 38, 39]. The proton: electron ratio belonging to the nicotine oxidation was specified from the slope of Ep-pH ${{E}_{p}-pH}$ curve, and a −64.0 mV per pH signifies the ratio of 1 (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symmetry of the electrode reaction was investigated by calculating the charge transfer coefficient ( α ) using the slope ( 2.3RT/[]1-αnF ${2.3RT/\left[\left(1-\alpha \right)nF\right]}$ ) of Ep4pt()mV- ${{E}_{p}{\rm \ }\left(mV\right)-}$ boldlboldoboldg(v,4ptmV/s) ${{\bf log}(v,{\rm \ }mV/s)}$ curve (Ep=97.40log(v)+ $({{E}_{p}=97.40{\bf log}(v)+}$ 692.90 $692.90$ (R 2 : 0.981)), and α was determined as 0.697 (Figure S4). This indicates an asymmetric behavior of the transition state regarding the applied potential, acting akin to a product‐like transition state [26, 38, 39]. The proton: electron ratio belonging to the nicotine oxidation was specified from the slope of Ep-pH ${{E}_{p}-pH}$ curve, and a −64.0 mV per pH signifies the ratio of 1 (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Amid electroanalytical techniques, electrodes modified with polymer films are acknowledged for their ability to improve the kinetics of electron transfer when compared to electrodes without any modifications. They provide numerous advantages involving enhanced sensitivity, high selectivity and stability, versatility, reusability, fast response, tunable properties, miniaturization and portability, straightforward manufacturing, reduced interference effect, excellent biocompatibility, signal amplification, and compatibility with various electrochemical techniques [23][24][25][26]. As a result, researchers are continuously exploring and developing novel polymer materials and modification approaches to further improve these electrodes for sensor development [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the conditions of lead film formation in many procedures described in the literature, it was observed that the potential applied to the electrode being the substrate for the film assumed a different value from − 0.65 V in the negative direction up to − 1.7 V (Bobrowski et al 2008;Bobrowski et al 2018;Deniz et al 2017;Gęca et al 2016;Grabarczyk and Adamczyk 2019;Korolczuk et al 2014;Tyszczuk-Rotko et al 2014). As for the adsorption of Ti (IV) complexes on the surface of the working electrode in various procedures described in the literature, the potential also changed in a wide range depending on the working electrode and the complex (Bobrowski et al 2009;Cui et al 2013;Croot 2011;Gawryś and Golimowski 2001;Gawryś and Golimowski 2003;Grabarczyk and Wasąg 2015;Pereira and Pereira 1999;Romanus et al1991;Stadlober et al 1996;Vukomanovic and Loon 1994;Wasąg and Grabarczyk 2016;Zhao et al 1995).…”
Section: Accumulation Potential and Timementioning
confidence: 99%
“…In recent years, the literature has described many different working electrodes which use the formation of metallic films, among others lead film electrodes (PbFE). The formation of these electrodes can take place both ex situ and in situ (Bobrowski et al 2008;Bobrowski et al 2018;Deniz et al 2017;Gęca et al 2016;Grabarczyk and Adamczyk 2019;Korolczuk et al 2014;Tyszczuk-Rotko et al 2014). In the case of in situ, we add the salt of the lead from which the film is to be formed to the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation